Penguatan Moderasi Beragama Di Pesantren Quran Di Kota Cilegon - Hasbullah, Hasbullah; Al Hakim, Muhaffazh; Albantani, Muhammad Sholehuddin (Ulumuddin: Jurnal Ilmu-ilmu Keislaman, 2023)
The goal of this study is to ascertain how religious moderation is being strengthened at the Pesantren Bany Syafii (PBS), which is situated in the center of a residential neighborhood in the city of Cilegon. Data for this qualitative study were gathered through observation, documentation, and interviews. The findings demonstrated that PBS had implemented religious moderation for students through the teaching of the kitab kuning supported by regular rituals like group prayer, recitation of the book, discussions, jam'iyah, and mutual assistance as well as the involvement of the students in extracurricular activities. Aside from that, santri are trained to respect everyone surrounding the boarding school, regardless of their differing religious beliefs. So, This learning on religious tolerance is complementary.